Sistem Pendukung Keputusan Calon Penerima BPJS-PBI Pada Dinas Sosial Kota Bengkulu Menggunakan Metode K-Nearest Neighbor (KNN) - Mahendra, Aziz Ali; Suranti, Dewi; Fredricka, Jhoanne (Jurnal Media Infotama, 2023)
Abstract-Health Social Security Organizing Agency for Contribution Assistance Recipient groups is assistance for the poor and disadvantaged people who are financed by the Government. The goal of the Health Social Security Administrative Body is to improve access and quality of health services for all underprivileged and incapable people to achieve optimal public health status effectively and efficiently. One of the problems faced by the Bengkulu City Social Service in determining beneficiaries of Health Social Security Administering Body assistance for the Contribution Assistance Beneficiary group is the process carried out by the Bengkulu City Social Service in making decisions on receiving Contribution assistance Health Social Security Administrative Body for poor families, still uses the manual method so it takes time. long to process. This decision support system for determining beneficiaries applies the K-Nearest Neighbor method to assist the selection process of citizens who are entitled to receive the Health Social Security Administrative Body so that it is easier to assess the criteria for residents. K-Nearest Neighbor can perform a mathematically based procedure to evaluate the values ​​of these criteria into an accurate description of the data classification. This decision support system is designed using the PHP Programming Language and MySQL Database. This decision support system can provide convenience for the Bengkulu City Social Service in determining beneficiaries of Health Social Security Administering Body assistance for groups of Contribution Assistance Recipients in Bengkulu City.